Learning Videos on Theme of Our Friend's Environment, Sub-Theme of Humans, and Elementary School Environment - Ni Nengah Ayu Wangi; Ni Wayan Rati; I Komang Sudarma (Universitas Pendidikan Ganesha, 2021)
Based on the problems found in the school where the researcher is known, the learning method used by the teacher is still predominantly using the lecture method, and the availability of media in schools is still very minimal. This study aims to create learning video product development for fifth-grade elementary school students and to develop learning videos for fifth-grade elementary school students whose validity has been tested. This research refers to the ADDIE development model procedure. The subjects of this study were material content experts, instructional design experts, instructional media experts, and fifth-grade elementary school students. The object of this research is the validity of the instructional videos. This study using a questionnaire method by providing assessment sheets to material content expert lecturers, learning design experts, instructional media experts, and fifth-grade elementary school students. The data used in this development research are qualitative and quantitative. The results of the validity test of the learning video obtained results: content experts obtained 93.33% results with very good qualifications, learning design experts obtained 89.09% results with good qualifications, learning media experts obtained 92.5% results with very good qualifications, and individual trials obtained a result of 98.6% with very good qualifications. Based on the results of the data analysis, it can be stated that this instructional video media is suitable for use in the theme of our friend's environment, the human sub-theme, and the fifth-grade elementary school environment.